Inscription on the Antarala of the Kalika Devi Temple - Temples of India Project Team (Jio Institute, 2024)
An inscription is found in the antarala (vestibule or antechamber) of the Kalika Devi or the Navdurga Temple. Based on palaeographic evidence, it can be said that the letters engraved belong to a later period.